Integrating DNA Encapsulates and Digital Microfluidics for Automated Data Storage in DNA - Antkowiak, Philipp L.; Koch, Julian; Nguyen, Bichlien; Stark, Wendelin J.; Strauss, Karin; Ceze, Luis; Grass, Robert N. (Small, 2022)
Using DNA as a durable, high-density storage medium with eternal format relevance can address a future data storage deficiency. The proposed storage format incorporates dehydrated particle spots on glass, at a theoretical capacity of more than 20 TB per spot, which can be efficiently retrieved without significant loss of DNA. The authors measure the rapid decay of dried DNA at room temperature and present the synthesis of encapsulated DNA in silica nanoparticles as a possible solution. In this form, the protected DNA can be readily applied to digital microfluidics (DMF) used to handle retrieval operations amenable to full automation. A storage architecture is demonstrated, which can increase the storage capacity of today's archival storage systems by more than three orders of magnitude: A DNA library containing 7373 unique sequences is encapsulated and stored under accelerated aging conditions (4 days at 70 °C, 50% RH) corresponding to 116 years at room temperature and the stored information is successfully recovered.